2008
DOI: 10.1021/ma800529d
|View full text |Cite
|
Sign up to set email alerts
|

Composition Control of Aromatic Copolyesters by Shearing

Abstract: Composition control of copolyester was examined by using hydrodynamically induced phase separation, during solution polymerization, of p-acetoxybenzoic acid and m-acetoxybenzoic acid (m-ABA). Polymerizations were carried out in liquid paraffin at 1.0% of concentration under shear flow. The polymers were obtained as precipitates formed via phase separation of oligomers and the subsequent polymerization in the precipitates. When the feed ratio of m-ABA (χ f ) was 20 mol %, the molar ratio of m-oxybenzoyl moiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…It has been reported previously that the stirring influenced the phase‐separation behavior of the oligomers and the apparent reaction rate of monomers, bringing about the change in the morphology and the composition of copolymers 31. The χ p value under stirring was 7.3 mol % and it was almost the same as that without stirring of 7.9 mol %.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…It has been reported previously that the stirring influenced the phase‐separation behavior of the oligomers and the apparent reaction rate of monomers, bringing about the change in the morphology and the composition of copolymers 31. The χ p value under stirring was 7.3 mol % and it was almost the same as that without stirring of 7.9 mol %.…”
Section: Resultsmentioning
confidence: 60%
“…In order to increase the N p av value and to decrease the diameter of the fiber, the stirring was applied to the polymerization of ABA with DABA at χ f of 15 mol % at a concentration of 1.5% in DBT at 320°C. It has been reported that the stirring accelerated the fibrillation of the POB whiskers to yield the fibrillated fine fibers 31. The precipitates were obtained under stirring at γ was 147 s −1 with the yield of 12%.…”
Section: Resultsmentioning
confidence: 94%
“…Wide‐angle X‐ray scattering (WAXS) was performed on a Rigaku Gaiger Flex with nickel‐filtered CuKα radiation (35 kV, 20 mA). Rate constants of the condensation reaction of AMBA and AABA were estimated kinetically by the measurements of eliminated acetic acid according to the previously reported procedure …”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the heterogeneous polycondensation which is the polymerization performed in multiple phases such as a solution phase and a solid phase has been developed for the precise control of not only the primary polymer structures but also their higher‐ordered structures. The heterogeneous polycondensation containing the reaction‐induced phase separation had provided sequence control of whiskers, dual self‐assemble polycondensation, and fractional polycondensation . Among them, the fractional polycondensation which is the polymerization to synthesize homopolymers chemoselectively as precipitates in the copolymerization system has a potential to control the composition of copolymers, and the composition control of aromatic copolyesters had been studied by using hydrodynamically induced phase separation during solution polymerization of p ‐acetoxybenzoic acid and m ‐acetoxybenzoic acid .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation